1978
DOI: 10.1136/jcp.31.9.837
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of presence of HBsAg undetectable by conventional radioimmunoassay in anti-HBc positive blood donors.

Abstract: SUMMARY Sera from two blood donors, one of whom was implicated in a case of post-transfusion hepatitis B, were found to be positive for anti-HBc and negative for HBsAg by conventional radioimmunoassay and were retested for HBsAg after concentration (pepsin digestion and polyethylene glycol precipitation). The presence of occult HBsAg was confirmed in both. These observations have implications for blood transfusion, and wider studies of anti-HBc in blood donors are recommended before the introduction of routine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…The observation that HBsAg can appear in the blood at least 35 days before anti-HBc antibody has already been reported [8][9][10]. The appearance of anti-HBc antibody gen erally occurs at the time of the first signs of clinical hepatitis, and it persists as a high titer for many years [10].…”
Section: Categories Of Casesmentioning
confidence: 98%
See 1 more Smart Citation
“…The observation that HBsAg can appear in the blood at least 35 days before anti-HBc antibody has already been reported [8][9][10]. The appearance of anti-HBc antibody gen erally occurs at the time of the first signs of clinical hepatitis, and it persists as a high titer for many years [10].…”
Section: Categories Of Casesmentioning
confidence: 98%
“…In chronic HBsAg carriers HBsAg levels dilfer substantially from one subject to another and may be very low, whereas the titers of anti-HBc in these cases are always high. Moreover, in the absence of HBsAg and anti-HBs the presence of antiHBc antibody at a high titer may indicate a low level of chronic HBV infection [7][8][9], There is also evidence to suggest that popu lations with anti-HBc are more likely to transmit NANB hepatitis than donors with out anti-HBc [2,6,12], Thus, testing for anti-HBc may provide important data on a blood donor popula tion. However, it cannot replace HBsAg screening since infectious blood donors would not be detected during the incubation period of hepatitis B.…”
Section: Categories Of Casesmentioning
confidence: 99%
“…Because it has been suggested that the occurrence in serum of anti-HBc alone, but at high titre could be associated with an undetectable amount, even by RIA, of HBsAg [13], we looked at this aspect. In fact the titres of anti-HBc, studied in 120 of our donors randomly selected, were low (see ta ble II) suggesting that they do not carry the HBsAg in undetectable amounts, although a direct proof of this assumption could be reached only using the method suggested by Harris et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a very low level of HBsAg has been shown in samples with anti-HBc activity in the absence of any detectable HBsAg and anti-HBs reactivities by the use of special techniques [5,9,14], The evidence suggests that failure to detect HBsAg in some blood with anti-HBc may be due to limita tions in the sensitivity of the test currently employed. We feel that by increasing the sensitivity it would be possible to detect most blood that may be clinically signifi cant, i.e., those that may have sufficient level of HBV to cause infection.…”
Section: Discussionmentioning
confidence: 99%